Evaluasi Penerapan Insinerator Sampah Skala Kecil di TPST Kabupaten Sidoarjo - Purwanta, Wahyu (Jurnal Teknologi Lingkungan, 2021)
ABSTRACT The waste's production rate in Sidoarjo Regency is estimated at 1,216 tpd. Around 464 tpd (ton per day) are transported to Jabon Landfill, and about 298 tpd are treated at the Integrated Garbage Treatment Center (TPST), 3R Treatment Center, and the Bank of Garbage. Therefore, there are still 454 tpd of waste that has not yet been managed, potentially harming the environment. The still limited garbage service level to be transported to the landfill has made the community take the initiative to process the garbage with incinerators placed at the existing TPST. These incinerators can reduce the waste up to 25% to 30% by weight of the waste that enters the TPST. In this research, ten incinerators were studied in the TPST. From the sample conditions obtained, almost all incinerators were operated below the technical standards required for optimum operation and minimum environmental impact. The combustion temperature is generally below 800 °C, the gas residence time is less than 2 seconds, and there is no turbulence. Therefore, the black smoke often occurs due to incomplete combustion. Air pollution control installations such as cyclones and scrubbers are malfunctioning and rusty due to high temperatures and acidic environments. Incinerator management hardly relies on community contributions. However, it is generally only enough for employee salaries. Furthermore, there is no incinerator maintenance. On the other hand, social conflicts due to incinerator smoke are reported to have not yet occurred because the location of TPST is generally still far from residential areas. Keywords: incinerator, small scale, operation, environmental   ABSTRAK Tingkat timbulan sampah Kabupaten Sidoarjo adalah 1.216 ton/hari, dimana sekitar 464 ton dibawa ke TPA Jabon dan 298 ton ditangani di TPST, TPS 3R, dan Bank Sampah. Hal ini berarti masih ada 454 ton sampah yang tidak terkelola dan berpotensi lari ke lingkungan. Masih terbatasnya tingkat pelayanan sampah untuk diangkut ke TPA telah membuat masyarakat berinisiatif mengolah sampahnya dengan insinerator yang ditempatkan di TPST yang ada. Keberadaan insinerator ini mampu mengurangi berat sampah hingga 25% hingga 30% berat sampah yang masuk ke TPST. Melalui penelitian terhadap sepuluh insinerator di TPST, diperoleh kondisi bahwa hampir semua insinerator beroperasi di bawah standar teknis yang dipersyaratkan bagi tercapainya operasi optimum dan minimnya dampak lingkungan. Suhu pembakaran umumnya berada di bawah 800 0C, waktu tinggal gas kurang dari 2 detik dan tidak terjadi turbulensi, sehingga sering terjadi asap yang hitam akibat pembakaran tidak sempurna. Kondisi instalasi pengendalian pencemaran udara seperti cyclone dan scrubber banyak yang tidak berfungsi dan berkarat akibat tidak tahan suhu tinggi dan lingkungan yang asam. Pengelolaan insinerator mengandalkan iuran warga namun umumnya hanya cukup untuk honor pekerja sehingga tidak ada untuk perawatan insinerator. Konflik sosial akibat asap insinerator belum terjadi karena lokasi TPST umumnya masih jauh dari permukiman warga. Kata Kunci:  insinerator, skala kecil, operasi, lingkungan